Legal Politics of Simplifying Political Parties in Indonesia (Case Study of 2004 – 2014 Election) - Mochammad Andry Wikra Wardhana Mamonto (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2019)
Combination of presidential government systems and multi-party systems as a system of Indonesian state has led to a government that does not effective and stable. The formulation of the problem which is the focus of the study in this paper, namely how is the legal politics of simplification of political parties in Indonesia for the period 2004 – 2014. The research method used in this study is normative. Based on the results of the study, the authors obtained answers to the existing problems, that the legal politics of simplifying political parties in Indonesia is democratic legal politics, but the legal politics of simplifying political parties in Indonesia should not only be directed at simplifying political parties in parliament, but also simplifying political parties in political parties participating in the general election.